2018
DOI: 10.1038/s41598-018-24509-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional landscape of Mycobacterium tuberculosis infection in macrophages

Abstract: Mycobacterium tuberculosis (Mtb) infection reveals complex and dynamic host-pathogen interactions, leading to host protection or pathogenesis. Using a unique transcriptome technology (CAGE), we investigated the promoter-based transcriptional landscape of IFNγ (M1) or IL-4/IL-13 (M2) stimulated macrophages during Mtb infection in a time-kinetic manner. Mtb infection widely and drastically altered macrophage-specific gene expression, which is far larger than that of M1 or M2 activations. Gene Ontology enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
94
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 43 publications
16
94
1
Order By: Relevance
“…Previous reports have shown that EGR1 regulates ATF3 expression in murine αT3-1 cells (Mayer, Dexheimer, Nishida, Kitajima, & Thiel, 2008). Both we and others have observed through global transcriptome profiling that challenge of macrophages with M. tuberculosis leads to an early upregulation of EGR1 (Kumar et al, 2015;Roy et al, 2018). In this study, we validated the early upregulation of EGR1 transcript in infected RAW264.7 ( Figure 2a) and BMDMs ( Figure 2b).…”
Section: Transcriptional Regulation Of Atf3 Is Dependent Upon Egr1 supporting
confidence: 74%
See 1 more Smart Citation
“…Previous reports have shown that EGR1 regulates ATF3 expression in murine αT3-1 cells (Mayer, Dexheimer, Nishida, Kitajima, & Thiel, 2008). Both we and others have observed through global transcriptome profiling that challenge of macrophages with M. tuberculosis leads to an early upregulation of EGR1 (Kumar et al, 2015;Roy et al, 2018). In this study, we validated the early upregulation of EGR1 transcript in infected RAW264.7 ( Figure 2a) and BMDMs ( Figure 2b).…”
Section: Transcriptional Regulation Of Atf3 Is Dependent Upon Egr1 supporting
confidence: 74%
“…It is ubiquitously expressed and is induced upon challenge of a variety of cell types by bacteria (de Klerk, Saroj, Wassing, Maudsdotter, & Jonsson, 2017). Both we and others have observed through global transcriptome profiling that challenge of macrophages with M. tuberculosis leads to an early upregulation of EGR1 (Kumar et al, 2015;Roy et al, 2018). Both we and others have observed through global transcriptome profiling that challenge of macrophages with M. tuberculosis leads to an early upregulation of EGR1 (Kumar et al, 2015;Roy et al, 2018).…”
Section: Transcriptional Regulation Of Atf3 Is Dependent Upon Egr1 mentioning
confidence: 70%
“…It is thought that Th2 cytokines such as IL-13 can cause inappropriate activation of macrophages and thus, undermine the Th1 response suitable for an intracellular pathogen like Mtb. 21 We also found increased levels of IL-17A, IP-10 and MIP1β in converters compared with nonconverters. IL-17A is associated with Th17 responses with a previous study from our laboratory showing contrasting findings (ie, increased IL-17A in TBR).…”
Section: Discussionsupporting
confidence: 53%
“…In the later stages and chronic disease, the infection is associated with responses mediated by M2 macrophages, whose weak microbicidal activity and ability to eliminate bacteria are linked to the occurrence of the lesions observed during disease evolution. [265][266][267][268][269] In leprosy, macrophages are the primary cells that exert microbicidal activity. Thus, the role of macrophages in the response to M. leprae has been widely described and is correlated with the expression of certain cytokines that are classical representatives of the cellular immune response, such as TNF-α and IFN-γ.…”
Section: Autophagymentioning
confidence: 99%